Silicon-carbon negative electrode material and preparation method thereof

By forming an inner and outer double-layer conductive network in the silicon carbon anode material, the problem of low conductivity of the silicon anode material is solved, the energy density and power density of the battery are improved, and more efficient electrochemical performance and longer cycle life are achieved.

CN119275257AActive Publication Date: 2025-01-07HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411195631.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-07
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The current silicon negative electrode materials have low conductivity, resulting in limited application in lithium-ion batteries and cannot meet the requirements of high energy density and high power density.

Method used

The first material is prepared by mixing and stirring heating of asphalt, metal powder and pore-forming agent, followed by chemical vapor deposition in a mixed atmosphere of silicon source gas and inert gas, and carbon encapsulation is carried out in a mixed atmosphere of carbon source gas and inert gas. The overlay treatment forms an inner and outer double-layer conductive network to improve the conductivity of silicon carbon negative electrode materials.

Benefits of technology

It significantly improves the conductivity of silicon-carbon anode material, improves the first-time Coulomb efficiency and cycle life of the battery, and simplifies the process and improves safety, making it suitable for large-scale commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275257A_ABST
    Figure CN119275257A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon negative electrode material and a preparation method thereof, and relates to the technical field of lithium ion batteries. The preparation method of the silicon-carbon negative electrode material comprises the following steps: S1, mixing, stirring and heating asphalt, metal powder and a pore-forming agent, cooling, crushing, grinding, and cleaning and drying by using a first organic solvent to form a first material; and S2, carrying out chemical vapor deposition on the first material in a mixed atmosphere of silicon source gas and inert gas, carrying out carbon coating treatment in a mixed atmosphere of carbon source gas and inert gas, cooling, and uniformly grinding to obtain the silicon-carbon negative electrode material, the silicon-carbon negative electrode material prepared by the method has excellent conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-carbon negative electrode material and a preparation method thereof. Background Art

[0002] As the excessive use of fossil energy causes air pollution and global warming, countries are increasingly demanding clean energy to achieve carbon neutrality goals. Compared with traditional energy storage systems, advanced lithium-ion batteries (LIBs) have become one of the most important alternative technologies for energy storage.

[0003] Lithium-ion batteries include negative electrode materials. However, conventional graphite negative electrode materials have a low theoretical capacity (372 mAh g -1 ), cannot meet the requirements of high energy density and high power density. Although silicon negative electrode materials have high theoretical lithium insertion capacity (Li 3.75 Si: 3579 mAh g -1 ), low operating voltage (<0.4V vs.Li / Li + ), abundant resources and environmental friendliness, it has gradually entered the application market. However, the inherent low conductivity of silicon material itself (~10 -3 S cm -1 ) has hindered the large-scale commercial application of silicon negative electrode materials. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the deficiencies in the prior art, the present invention provides a silicon-carbon negative electrode material and a preparation method thereof, which solves the technical problem of low electrical conductivity of the prior silicon negative electrode material.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] In one aspect, the present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0009] S1, mixing asphalt, metal powder and pore-forming agent, stirring and heating, cooling, crushing and grinding, washing and drying with a first organic solvent to form a first material;

[0010] The mass ratio of the asphalt to the metal powder is 10:1 to 2:1; the mass ratio of the asphalt to the pore-forming agent is 1:2 to 1:10; the stirring time is 1 to 10 hours; the heating temperature is 300 to 500° C., and the heating time is 1 to 6 hours;

[0011] S2, subjecting the first material to chemical vapor deposition in a mixed atmosphere of silicon source gas and inert gas, and then subjecting the first material to carbon coating in a mixed atmosphere of carbon source gas and inert gas, and grinding the first material uniformly after cooling to obtain a silicon-carbon negative electrode material;

[0012] The temperature of the chemical vapor deposition is 500-700° C., and the time is 1-6 hours. The temperature of the carbon coating treatment is 600-700° C., and the time is 1-4 hours.

[0013] The preparation method of the silicon-carbon negative electrode material of the present invention comprises the following steps: asphalt, metal powder and a pore-forming agent are selected, mixed, stirred and heated, cooled, crushed and then ground to obtain a first material, wherein the metal powder forms a first conductive metal layer in the first material, and then the first material is subjected to chemical vapor deposition in a mixed atmosphere of a silicon source gas and an inert gas, and then carbon-coated in a mixed atmosphere of a carbon source gas and an inert gas, and then ground evenly after cooling to obtain a silicon-carbon negative electrode material, wherein the carbon source gas fills the holes not filled by the silicon source gas to form a complete second conductive layer, so that the prepared silicon-carbon negative electrode material includes an inner and outer double-layer conductive network, thereby ensuring the conductivity of the silicon-carbon negative electrode material.

[0014] Preferably, S1 further comprises nitrogen doping treatment of the asphalt, wherein the nitrogen doping treatment comprises dissolving the asphalt and the nitrogen-containing organic polymer in a second organic solvent, stirring, and then freeze-drying and grinding.

[0015] Preferably, the nitrogen-containing organic polymer is selected from at least one of polyimide, polysulfonamide and melamine;

[0016] and / or, the mass ratio of the asphalt to the nitrogen-containing organic polymer is 1:1 to 1:10;

[0017] and / or, the mass ratio of the sum of the mass of the asphalt and the nitrogen-containing organic polymer to the mass of the second organic solvent is 1:5 to 1:10;

[0018] and / or, the second organic solvent is selected from at least one of N-methylpyrrolidone, n-hexane, xylene, carbon disulfide and carbon tetrachloride;

[0019] And / or, the freeze-drying temperature is -30°C to -50°C;

[0020] And / or, the freeze-drying time is 12h to 24h.

[0021] After the asphalt is nitrogen-doped and freeze-dried according to the above process, the first material obtained has a high specific surface area, uniform pore volume and pore size, and a large number of reaction active sites. The reaction sites allow the silicon source gas to better adhere to nucleation and grow, thereby increasing the capacity of the material. At the same time, the metal powder can provide attachment sites for the silicon source, facilitating the uniform deposition of silicon, thereby ensuring the cycle and rate performance of the silicon-carbon negative electrode material.

[0022] Preferably, the preparation method further comprises spraying pyrolysis treatment on the silicon-carbon negative electrode material, wherein the spraying pyrolysis treatment comprises mixing and stirring an organic carbon source, a reducing organic solvent and the silicon-carbon negative electrode material, ultrasonically treating the mixture, and spraying and pyrolyzing the mixture in a high temperature atmosphere;

[0023] The spray pyrolysis temperature is 300-500° C., and the spray flow rate is 1-10 mL / min.

[0024] Preferably, the organic carbon source is selected from at least one of citric acid, acetic acid, oxalic acid, formic acid, propionic acid and stearic acid;

[0025] and / or, the reducing organic solvent is selected from at least one of ethanol, ether, dichloromethane, acetone and xylene;

[0026] And / or, the mass ratio of the organic carbon source to the reducing organic solvent is 1:5 to 1:20;

[0027] And / or, the mass ratio of the total mass of the organic carbon source and the reducing organic solvent to the silicon-carbon negative electrode material is 1:1 to 10:1;

[0028] And / or, the stirring reaction time is 1 to 4 hours, and the ultrasonic treatment time is 10 to 30 minutes.

[0029] After the spray pyrolysis treatment, the organic carbon source fills the holes that are not filled by the silicon source gas again to form a complete coating layer, which not only limits the volume expansion of the silicon-carbon negative electrode material, ensures the cycle and rate performance of the silicon-carbon negative electrode material, but also improves the conductivity of the silicon-carbon negative electrode material. The above-mentioned spray pyrolysis treatment avoids the conversion of amorphous silicon into crystalline silicon during high-temperature carbon coating, and the reducing organic solvent prevents the nano-silicon particles from being oxidized during pyrolysis, thereby ensuring the cycle and rate performance of the silicon-carbon negative electrode material.

[0030] Preferably, the asphalt in step S1 is selected from coal tar asphalt, petroleum asphalt and natural asphalt, and the D50 of the asphalt is 3 to 5 mm;

[0031] And / or, the metal powder in step S1 is selected from at least one of tin, bismuth, indium and lithium;

[0032] And / or, the pore-forming agent in step S1 is selected from at least one of phosphoric acid, zinc chloride, potassium hydroxide and potassium carbonate.

[0033] Preferably, the silicon source gas in step S2 is selected from at least one of monosilane or its homologues;

[0034] and / or, the inert gas is selected from at least one of helium, argon and nitrogen;

[0035] And / or, the carbon source gas is selected from at least one of acetylene, methane or their homologues.

[0036] Preferably, the volume ratio of the inert gas to the silicon source gas is 4:1 to 1:1.

[0037] Preferably, the volume ratio of the inert gas to the carbon source gas is 4:1 to 1:1.

[0038] On the other hand, the present invention provides a silicon-carbon negative electrode material prepared by the preparation method described in the first aspect, wherein the resistivity of the silicon-carbon negative electrode material is 3.9Ω·cm to 5.1Ω·cm, and the first coulombic efficiency is 91.9% to 93.1%. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 This is the SEM test result of the silicon-carbon negative electrode material prepared in Example 1 of the present invention.

[0041] Figure 2 The charge and discharge capacity test results of the silicon-carbon negative electrode material prepared in Example 1 of the present invention and the material in Comparative Example 1.

[0042] Figure 3 The cycle performance test results of the silicon-carbon negative electrode material prepared in Example 1 of the present invention and the material of Comparative Example 1 are shown. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The embodiments of the present application provide a silicon-carbon negative electrode material and a preparation method thereof, thereby solving the technical problems of low electrical conductivity and poor cycle and rate performance of existing silicon negative electrode materials.

[0045] The technical solution in the embodiment of the present application is to solve the above technical problems, and the overall idea is as follows:

[0046] Silicon material in lithium-intercalated state (Li 3.75Si) will produce a huge volume expansion (>300%), leading to the formation of an unstable solid electrolyte interphase (SEI), particle crushing, and ultimately severe capacity decay during the battery cycle. The pre-lithiation of silicon oxide materials, including direct addition of lithium powder, electrochemical pre-embedding of lithium, etc., can improve the first coulombic efficiency to a certain extent. However, the above modification methods still have many problems. At this stage, the pre-lithiation process has problems such as high cost, complex process, and easy explosion in the pre-lithiation process, so it is difficult to apply in actual production.

[0047] Therefore, designing and developing a new silicon-carbon material that can not only improve the first coulombic efficiency but also maintain electrode stability and improve cycle life is a key technology for realizing the practical application of silicon-based negative electrode materials.

[0048] The preparation method of the silicon-carbon negative electrode material of the present invention comprises the following steps: asphalt, metal powder and a pore-forming agent are selected, mixed, stirred and heated, cooled, crushed and then ground to obtain a first material, wherein the metal powder forms a first conductive metal layer in the first material, and then the first material is subjected to chemical vapor deposition in a mixed atmosphere of a silicon source gas and an inert gas, and then carbon-coated in a mixed atmosphere of a carbon source gas and an inert gas, and then ground evenly after cooling to obtain a silicon-carbon negative electrode material, wherein the carbon source gas fills the holes not filled by the silicon source gas to form a complete second conductive layer, so that the prepared silicon-carbon negative electrode material includes an inner and outer double-layer conductive network, thereby ensuring the conductivity of the silicon-carbon negative electrode material.

[0049] The present invention also performs nitrogen doping and freeze-drying on asphalt to obtain a first material with high specific surface area, uniform pore volume and pore size, and a large number of reaction active sites. The reaction sites allow the silicon source gas to better adhere to nucleation and grow, thereby increasing the capacity of the material. At the same time, the metal powder can provide attachment sites for the silicon source, facilitating the uniform deposition of silicon, thereby ensuring the cycle and rate performance of the silicon-carbon negative electrode material.

[0050] After the spray pyrolysis treatment, the organic carbon source fills the holes that are not filled by the silicon source gas again to form a complete coating layer, which not only limits the volume expansion of the silicon-carbon negative electrode material, ensures the cycle and rate performance of the silicon-carbon negative electrode material, but also improves the conductivity of the silicon-carbon negative electrode material. The above-mentioned spray pyrolysis treatment avoids the conversion of amorphous silicon into crystalline silicon during high-temperature carbon coating, and the reducing organic solvent prevents the nano-silicon particles from being oxidized during pyrolysis, thereby ensuring the cycle and rate performance of the silicon-carbon negative electrode material.

[0051] Therefore, the silicon-carbon negative electrode material prepared by the present invention has good conductivity, can effectively improve the initial coulombic efficiency and cycle life of the battery, and has a simple process and high safety, which is conducive to the promotion and application of silicon-carbon negative electrode materials.

[0052] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0053] Example 1

[0054] This embodiment provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0055] S1. Mix 100 g of coal tar pitch with a D50 of 3 mm and 100 g of polyimide in a beaker containing 1000 g of N-methylpyrrolidone solvent, stir for 2 h, take out and place in a freeze dryer, freeze-dry at -50°C and normal pressure for 24 h, then take out and grind to obtain material A;

[0056] S2, taking 100g of material A, 10g of tin metal powder and 200g of potassium hydroxide, mixing them in a three-dimensional mixer for 2h, taking them out and putting them in a tube furnace, keeping them at 350°C for 2h, grinding them after cooling, placing them in a beaker containing 1550g of n-hexane solvent, stirring and washing them for 2h, and drying them to obtain material B;

[0057] S3, 20g of material B was placed in a rotary furnace, silane gas and argon gas were introduced, the silane gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 500°C for 2h for chemical vapor deposition, then acetylene gas and argon gas were introduced, the acetylene gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 700°C for 4h, cooled to room temperature, and then placed in a mechanical mill and ground to D50 of 5μm to obtain material C;

[0058] S4. Place 100 g of material C and 100 g of citric acid in 500 g of anhydrous ethanol, stir to react for 2 h, then ultrasonically treat for 30 min, spray the suspension at 500 °C with a spraying rate of 10 mL / min, and obtain material D after cooling, which is the silicon-carbon negative electrode material.

[0059] The present invention first forms nitrogen-doped asphalt, forms a metal element-doped carbon matrix by activation and pore formation, introduces a silicon source and a carbon source, and finally uses an organic carbon source and a reducing organic solvent for mixed stirring and ultrasonic treatment to perform spray pyrolysis to form a silicon-carbon negative electrode material with excellent cycle and rate performance and good conductivity.

[0060] Asphalt is cheap, has large reserves and a low softening point, making it a good carbon matrix material;

[0061] Nitrogen-doped carbon materials have high specific surface area, uniform pore volume and pore size, and a large number of reactive sites. The reactive sites allow silicon source gas to better attach and nucleate and grow, thereby increasing the capacity of the material. Metal powder can provide attachment sites for silicon source gas, facilitating uniform deposition and further improving the conductivity of the material. Organic carbon sources can fill the holes that are not filled by silicon source gas to form a complete coating layer, limit the volume expansion of the material, and improve the conductivity. Spray pyrolysis can avoid the conversion of amorphous silicon into crystalline silicon during carbon coating at high temperatures, thereby affecting the material's cycle and rate performance. Reducing organic solvents can prevent nano-silicon particles from being oxidized during pyrolysis. The conductive network formed by the inner and outer double layers is also beneficial to the electrochemical stability of the material.

[0062] Example 2

[0063] This embodiment provides a method for preparing a novel silicon-carbon negative electrode material, comprising the following steps:

[0064] S1, 100g of coal tar pitch with a D50 of 3mm and 200g of polyimide were mixed in a beaker containing 3000g of N-methylpyrrolidone solvent, stirred for 2h, taken out and placed in a freeze dryer, freeze-dried at -50°C for 24h, and then taken out and ground to obtain material A;

[0065] S2, taking 100 g of material A, 25 g of tin metal powder and 1000 g of potassium hydroxide, mixing them in a three-dimensional mixer for 2 h, taking them out and putting them in a tube furnace, keeping them at 350° C. for 2 h, grinding them after cooling, placing them in a beaker containing 6000 g of n-hexane solvent, stirring and washing them for 2 h, and drying them to obtain material B;

[0066] S3, 20g of material B was placed in a rotary furnace, silane gas and argon gas were introduced, the silane gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 500°C for 2h for chemical vapor deposition, then acetylene gas and argon gas were introduced, the acetylene gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 700°C for 4h, cooled to room temperature, and then placed in a mechanical mill and ground to D50 of 5μm to obtain material C;

[0067] S4. Place 100 g of material C and 100 g of citric acid in 600 g of anhydrous ethanol, stir to react for 2 h, then ultrasonically treat for 30 min, spray the suspension at 500 °C with a spraying rate of 10 mL / min, and obtain material D after cooling, which is the silicon-carbon negative electrode material.

[0068] Example 3

[0069] This embodiment provides a method for preparing a novel silicon-carbon negative electrode material, comprising the following steps:

[0070] S1, 100g of coal tar pitch with a D50 of 3mm and 100g of polyimide were mixed in a beaker containing 1000g of N-methylpyrrolidone solvent, stirred for 2h, taken out and placed in a freeze dryer, freeze-dried at -50°C for 24h, and then taken out and ground to obtain material A;

[0071] S2, taking 100g of material A, 50g of lithium metal powder and 500g of potassium hydroxide, mixing them in a three-dimensional mixer for 4h, taking them out and putting them in a tube furnace, keeping them at 400°C for 2h, grinding them after cooling, placing them in a beaker containing 4000g of n-hexane solvent, stirring and washing them for 2h, and drying them to obtain material B;

[0072] S3, 20g of material B was placed in a rotary furnace, silane gas and argon gas were introduced, the silane gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 500°C for 2h for chemical vapor deposition, then acetylene gas and argon gas were introduced, the acetylene gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 700°C for 4h, cooled to room temperature, and then placed in a mechanical mill and ground to D50 of 5μm to obtain material C;

[0073] S4. Place 100 g of material C and 100 g of citric acid in 500 g of anhydrous ethanol, stir to react for 2 h, then ultrasonically treat for 30 min, spray the suspension at 500 °C with a spraying rate of 10 mL / min, and obtain material D after cooling, which is the silicon-carbon negative electrode material.

[0074] Example 4

[0075] This embodiment provides a method for preparing a novel silicon-carbon negative electrode material, comprising the following steps:

[0076] S1, 100g of coal tar pitch with a D50 of 3mm and 100g of polyimide were mixed in a beaker containing 1000g of N-methylpyrrolidone solvent, stirred for 2h, taken out and placed in a freeze dryer, freeze-dried at -50°C for 24h, and then taken out and ground to obtain material A;

[0077] S2, taking 100g of material A, 10g of indium metal powder and 200g of potassium hydroxide, mixing them in a three-dimensional mixer for 2h, taking them out and putting them in a tube furnace, keeping them at 350°C for 2h, grinding them after cooling, placing them in a beaker containing 1550g of n-hexane solvent, stirring and washing them for 2h, and drying them to obtain material B;

[0078] S3, 50g of material B is placed in a rotary furnace, and silane gas and argon gas are introduced, the silane gas flow rate is 5L / h, the argon gas flow rate is 20L / h, and the furnace speed is 1r / min. It is kept at 600°C for 4h for chemical vapor deposition, and then acetylene gas and argon gas are introduced, the acetylene gas flow rate is 5L / h, and the argon gas flow rate is 20L / h, and the furnace speed is 1r / min. Keep warm at 700°C for 4h, cool to room temperature, and then place it in a mechanical mill and grind it to D50 of 5μm to obtain material C;

[0079] S4. Place 100 g of material C and 100 g of citric acid in 500 g of anhydrous ethanol, stir to react for 2 h, then ultrasonically treat for 30 min, spray the suspension at 500 °C with a spraying rate of 10 mL / min, and obtain material D after cooling, which is the silicon-carbon negative electrode material.

[0080] Comparative Example 1

[0081] This comparative example provides a commercial SiO / C material (KSP-1 from Hunan Jinsi Technology Co., Ltd.) as a negative electrode material.

[0082] Comparative Example 2

[0083] This comparative example provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0084] S1, 100g of coal tar pitch with a D50 of 3mm and 100g of polyimide were mixed in a beaker containing 1000g of N-methylpyrrolidone solvent, stirred for 2h, taken out and placed in a freeze dryer, freeze-dried at -50°C for 24h, and then taken out and ground to obtain material A;

[0085] S2, taking 100 g of material A and 200 g of potassium hydroxide, mixing them in a three-dimensional mixer for 2 h, taking them out and putting them in a tube furnace, keeping them at 350° C. for 2 h, grinding them after cooling, placing them in a beaker containing 1550 g of n-hexane solvent, stirring and washing them for 2 h, and then drying them to obtain material B;

[0086] S3, 20g of material B was placed in a rotary furnace, silane gas and argon gas were introduced, the silane gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 500°C for 2h for chemical vapor deposition, then acetylene gas and argon gas were introduced, the acetylene gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 700°C for 4h, cooled to room temperature, and then placed in a mechanical mill and ground to D50 of 5μm to obtain material C;

[0087] S4. Place 100 g of material C and 100 g of citric acid in 500 g of anhydrous ethanol, stir to react for 2 h, then ultrasonically treat for 30 min, spray the suspension at 500 °C with a spraying rate of 10 mL / min, and obtain material D after cooling.

[0088] Comparative Example 3

[0089] This comparative example provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0090] S1, take 100g of coal tar pitch with D50 of 3mm, 10g of tin metal powder, and 200g of potassium hydroxide, mix them, place them in a three-dimensional mixer and mix them for 2h, take them out and put them in a tube furnace, keep them at 350℃ for 2h, grind them after cooling, place them in a beaker containing 1550g of n-hexane solvent, stir and wash them for 2h, and then dry them to obtain material B;

[0091] S2, 20g of material B was placed in a rotary furnace, silane gas and argon gas were introduced, the silane gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 500°C for 2h for chemical vapor deposition, then acetylene gas and argon gas were introduced, the acetylene gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 700°C for 4h, cooled to room temperature, and then placed in a mechanical mill and ground to D50 of 5μm to obtain material C;

[0092] S3. Place 100 g of material C and 100 g of citric acid in 500 g of anhydrous ethanol, stir to react for 2 h, then ultrasonically treat for 30 min, spray the suspension at 500 °C with a spraying rate of 10 mL / min, and obtain material D after cooling, which is the silicon-carbon negative electrode material.

[0093] Comparative Example 4

[0094] This comparative example provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0095] S1, 100g of coal tar pitch with a D50 of 3mm and 100g of polyimide were mixed in a beaker containing 1000g of N-methylpyrrolidone solvent, stirred for 2h, taken out and placed in a freeze dryer, freeze-dried at -50°C for 24h, and then taken out and ground to obtain material A;

[0096] S2, taking 100g of material A, 10g of tin metal powder and 200g of potassium hydroxide, mixing them in a three-dimensional mixer for 2h, taking them out and putting them in a tube furnace, keeping them at 350°C for 2h, grinding them after cooling, placing them in a beaker containing 1550g of n-hexane solvent, stirring and washing them for 2h, and drying them to obtain material B;

[0097] S3. Place 20g of material B in a rotary furnace, introduce silane gas and argon gas, the silane gas flow rate is 5L / h, the argon gas flow rate is 5L / h, and keep warm at 500°C for 2h under the condition of a furnace speed of 1r / min for chemical vapor deposition, then introduce acetylene gas and argon gas, the acetylene gas flow rate is 5L / h, the argon gas flow rate is 5L / h, and keep warm at 700°C for 4h under the condition of a furnace speed of 1r / min, cool to room temperature, and then place it in a mechanical mill and grind it to D50 of 5μm to obtain material C, which is a silicon-carbon negative electrode material.

[0098] Comparative Example 5

[0099] The specific steps include:

[0100] S1, 100g of coal tar pitch with a D50 of 3mm and 100g of polyimide were mixed in a beaker containing 1000g of N-methylpyrrolidone solvent, stirred for 2h, taken out, dried for 24h and ground to obtain material A;

[0101] S2, taking 100g of material A, 10g of tin metal powder and 200g of potassium hydroxide, mixing them in a three-dimensional mixer for 2h, taking them out and putting them in a tube furnace, keeping them at 350°C for 2h, grinding them after cooling, placing them in a beaker containing 1550g of n-hexane solvent, stirring and washing them for 2h, and drying them to obtain material B;

[0102] S3, 20g of material B was placed in a rotary furnace, silane gas and argon gas were introduced, the silane gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 500°C for 2h for chemical vapor deposition, then acetylene gas and argon gas were introduced, the acetylene gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 700°C for 4h, cooled to room temperature, and then placed in a mechanical mill and ground to D50 of 5μm to obtain material C;

[0103] S4. Place 100 g of material C and 100 g of citric acid in 500 g of anhydrous ethanol, stir to react for 2 h, then ultrasonically treat for 30 min, spray the suspension at 500 °C with a spraying rate of 10 mL / min, and obtain material D after cooling, which is the silicon-carbon negative electrode material.

[0104] Comparative Example 6

[0105] The specific steps include:

[0106] S1. Place 100 g of coal tar pitch with a D50 of 3 mm in a freeze dryer, freeze-dry at -50°C and normal pressure for 24 h, then take out and grind to obtain material A;

[0107] S2, taking 100g of material A, 10g of tin metal powder and 200g of potassium hydroxide, mixing them in a three-dimensional mixer for 2h, taking them out and putting them in a tube furnace, keeping them at 350°C for 2h, grinding them after cooling, placing them in a beaker containing 1550g of n-hexane solvent, stirring and washing them for 2h, and drying them to obtain material B;

[0108] S3, 20g of material B was placed in a rotary furnace, silane gas and argon gas were introduced, the silane gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 500°C for 2h for chemical vapor deposition, then acetylene gas and argon gas were introduced, the acetylene gas flow rate was 5L / h, the argon gas flow rate was 5L / h, and the furnace speed was 1r / min at 700°C for 4h, cooled to room temperature, and then placed in a mechanical mill and ground to D50 of 5μm to obtain material C;

[0109] S4. Place 100 g of material C and 100 g of citric acid in 500 g of anhydrous ethanol, stir to react for 2 h, then ultrasonically treat for 30 min, spray the suspension at 500 °C with a spraying rate of 10 mL / min, and obtain material D after cooling, which is the silicon-carbon negative electrode material.

[0110] Test example

[0111] The silicon-carbon negative electrode material prepared in Example 1 was subjected to SEM testing, and the results are as follows: Figure 1 As shown. Figure 1 It can be seen that the particle size of the silicon-carbon negative electrode material prepared in Example 1 is relatively uniform, and the particle size is about 6 μm.

[0112] The silicon-carbon negative electrode materials of Examples 1-4, Comparative Examples 2-6 and the commercial SiO / C material of Comparative Example 1 were respectively used as negative electrode active materials, and the mass ratio of negative electrode active material: conductive agent SP: binder LA133 was 8:1:1 for slurry mixing and coating, and CR2016 button batteries were assembled. The electrolyte used was 1 mol / L LiPF6 EC+DMC (mass ratio 1:1) solution, and the electrochemical performance test was carried out. The results are shown in Tables 1 and Figure 2-3 shown.

[0113] Table 1 Electrochemical performance test results of silicon-carbon negative electrode materials of Examples 1-4 and Comparative Examples 1-6

[0114]

[0115] From Table 1, it can be seen from the comparison between Example 1 and Comparative Example 1 that the resistivity of the silicon-carbon negative electrode material prepared in the present application is lower than that of the negative electrode material sold on the market. From Comparative Example 2, it can be seen that the silicon-carbon negative electrode material prepared without tin-containing metal powder has a higher resistivity and poorer cycle and rate performance. This is because the metal powder can provide an attachment site for the silicon source gas, which facilitates the uniform deposition of silicon, thereby improving its first discharge specific capacity, first charge specific capacity, and first coulomb efficiency. Metal powder can further improve the conductivity of the material, so its resistivity is low.

[0116] It can be seen from Example 1 and Comparative Examples 3, 5, and 6 that the silicon-carbon negative electrode material prepared by simultaneously nitrogen doping and freeze-drying coal tar pitch has excellent cycle and rate performance. This is because after the pitch is nitrogen doped and freeze-dried, the first material obtained under the synergistic effect of nitrogen doping and freeze-drying has a high specific surface area, uniform pore volume and pore size, and a large number of reaction active sites, thereby ensuring the cycle and rate performance of the silicon-carbon negative electrode material.

[0117] It can be seen from Example 1 and Comparative Example 4 that the silicon-carbon negative electrode material prepared by spray pyrolysis of the material without using a reducing organic solvent has poor cycle and rate performance. This is because spray pyrolysis can avoid the conversion of amorphous silicon into crystalline silicon during carbon coating at high temperature, thereby affecting the cycle and rate performance of the material. The reducing organic solvent can prevent the nano-silicon particles from being oxidized during pyrolysis, thereby affecting the cycle and rate performance of the material.

[0118] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0119] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The steps include: S1, mixing asphalt, metal powder and pore-forming agent, stirring and heating, cooling, crushing and grinding, washing and drying with a first organic solvent to form a first material; The mass ratio of the asphalt to the metal powder is 10:1 to 2:1; the mass ratio of the asphalt to the pore-forming agent is 1:2 to 1:10; the stirring time is 1 to 10 hours; the heating temperature is 300 to 500° C., and the heating time is 1 to 6 hours; S2, subjecting the first material to chemical vapor deposition in a mixed atmosphere of silicon source gas and inert gas, and then subjecting the first material to carbon coating in a mixed atmosphere of carbon source gas and inert gas, and grinding the first material uniformly after cooling to obtain a silicon-carbon negative electrode material; The temperature of the chemical vapor deposition is 500-700° C., and the time is 1-6 hours. The temperature of the carbon coating treatment is 600-700° C., and the time is 1-4 hours.

2. The preparation method according to claim 1, characterized in that The S1 also includes nitrogen doping treatment of the asphalt, and the nitrogen doping treatment includes dissolving the asphalt and the nitrogen-containing organic polymer in a second organic solvent, stirring, and then freeze-drying and grinding.

3. The preparation method according to claim 2, characterized in that: The nitrogen-containing organic polymer is selected from at least one of polyimide, polysulfonamide and melamine; and / or, the mass ratio of the asphalt to the nitrogen-containing organic polymer is 1:1 to 1:10; and / or, the mass ratio of the sum of the mass of the asphalt and the nitrogen-containing organic polymer to the mass of the second organic solvent is 1:5 to 1:10; and / or, the second organic solvent is selected from at least one of N-methylpyrrolidone, n-hexane, xylene, carbon disulfide and carbon tetrachloride; And / or, the freeze-drying temperature is -30°C to -50°C; And / or, the freeze-drying time is 12h to 24h.

4. The preparation method according to claim 1 or 2, characterized in that: The preparation method further comprises spraying pyrolysis treatment on the silicon-carbon negative electrode material, wherein the spraying pyrolysis treatment comprises mixing and stirring an organic carbon source, a reducing organic solvent and the silicon-carbon negative electrode material, ultrasonically treating the mixture, and spraying and pyrolyzing the mixture in a high temperature atmosphere; The spray pyrolysis temperature is 300-500° C., and the spray flow rate is 1-10 mL / min.

5. The preparation method according to claim 4, characterized in that: The organic carbon source is selected from at least one of citric acid, acetic acid, oxalic acid, formic acid, propionic acid and stearic acid; and / or, the reducing organic solvent is selected from at least one of ethanol, ether, dichloromethane, acetone and xylene; And / or, the mass ratio of the organic carbon source to the reducing organic solvent is 1:5 to 1:20; And / or, the mass ratio of the total mass of the organic carbon source and the reducing organic solvent to the silicon-carbon negative electrode material is 1:1 to 10:1; And / or, the stirring reaction time is 1 to 4 hours, and the ultrasonic treatment time is 10 to 30 minutes.

6. The preparation method according to claim 1, characterized in that: In step S1, the asphalt is selected from coal tar asphalt, petroleum asphalt and natural asphalt, and the D50 of the asphalt is 3 to 5 mm; And / or, the metal powder in step S1 is selected from at least one of tin, bismuth, indium and lithium; And / or, the pore-forming agent in step S1 is selected from at least one of phosphoric acid, zinc chloride, potassium hydroxide and potassium carbonate.

7. The preparation method according to claim 1, characterized in that: In step S2, the silicon source gas is selected from at least one of monosilane or its homologues; and / or, the inert gas is selected from at least one of helium, argon and nitrogen; And / or, the carbon source gas is selected from at least one of acetylene, methane or their homologues.

8. The preparation method according to claim 1, characterized in that: The volume ratio of the inert gas to the silicon source gas is 4:1 to 1:

1.

9. The preparation method according to claim 1, characterized in that: The volume ratio of the inert gas to the carbon source gas is 4:1 to 1:

1.

10. A silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The resistivity of the silicon-carbon negative electrode material is 3.9Ω·cm to 5.1Ω·cm, and the first coulomb efficiency is 91.9% to 93.1%.

Citation Information

Patent Citations

  • Tin-based nanoparticle-carbon composite material, and preparation method and application thereof

    CN106505188A

  • Silica material and treatment method thereof, and secondary battery negative electrode

    CN113422021A

  • Preparation method and application of amorphous silicon-based negative electrode material

    CN116281943A

  • Tin-carbon sodium ion battery negative electrode material as well as preparation method and application thereof

    CN116706019A

  • Silicon-carbon negative electrode material, negative electrode plate and secondary battery

    CN117174862A